Optimization of the Forward‐Osmosis Performance with a Low‐Concentration Draw Solution Using Response Surface Modeling. Issue 7 (26th May 2021) - Karunakaran, Aghilesh; Mungray, Alka A.; Agarwal, Smriti; Garg, Manoj Chandra
Abstract: Forward osmosis (FO) has recently gained interest in wastewater treatment and seawater and brackish groundwater desalination. Response surface methodology (RSM) was used for the prediction and optimization of the FO process using a low‐concentration draw solution (DS). The process variables were the feed solution (FS) temperature, the DS concentration, and the FS concentration. These variables were subjected to regression models and had R 2 values > 0.9. The FS temperature had a negative impact on the weight transfer from the DS, while the FS and DS concentrations had a direct correlation with the performance. At an FS temperature of 29 °C, the DS at 13 986 mg L −1 and the FS at 1702 mg L −1 produced the best results, thereby lowering the DS regeneration costs. Under this condition, the models were experimentally validated, confirming the predictive ability of the models. Abstract : Central composite design and response surface methodology were used to model the performance of a low‐concentration draw solution (DS) for the forward osmosis process. Regression equations were generated to evaluate the most influential parameters: the feed solution (FS) and DS concentrations and the FS temperature. Optimization and validation of the models was carried out with actual results.